2013
DOI: 10.1021/ja4002025
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Supramolecular Engineering of Hydrogen-Bonded Nanostructures at Surfaces: Predicting Self-Assembly in 2D

Abstract: We report a joint computational and experimental study on the concentration-dependent self-assembly of a flat C3-symmetric molecule at surfaces. As a model system we have chosen a rigid molecular module, 1,3,5-tris(pyridine-4-ylethynyl)benzene, which can undergo self-association via hydrogen bonding (H-bonding) to form ordered 2D nanostructures. In particular, the lattice Monte Carlo method, combined with density functional calculations, was employed to explore the spontaneous supramolecular organization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
147
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 97 publications
6
147
2
Order By: Relevance
“…7,10,15 In the adopted approach the basic molecular building block consisted of four interconnected segments arranged in a tripod with a core and three arms of equal length (one segment each). One molecular segment was allowed to occupy one adsorption site on a triangular lattice representing a (111) crystalline surface.…”
Section: The Model and Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,15 In the adopted approach the basic molecular building block consisted of four interconnected segments arranged in a tripod with a core and three arms of equal length (one segment each). One molecular segment was allowed to occupy one adsorption site on a triangular lattice representing a (111) crystalline surface.…”
Section: The Model and Computationmentioning
confidence: 99%
“…7,10,15,[22][23][24][25][26] This approach allows for selective observation of the 2D structures formed by just one type of molecular conformer without interference of the remaining ones. Such information can be especially important when a molecule with fixed position of interaction centers (no ratability is allowed) is to be synthesized to create an adsorbed superstructure with predefined morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] Polymorphs on 2D surfaces that arise from ad ifference in the concentration of the solution phase has attracted considerable attention,s ince it provides important insights into thermodynamic properties of surface-confined self-assemblies. [41][42][43][44][45] De Feyter et al have rationally interpreted an origin of polymorphs by considering the surface density of two different phases and the adsorption energiesp er molecule. [46] Althought he concentration dependence of such phaset ransitions between two or more different orderings hasb een well documented, much less is known about the mechanism that underlies ordering formation that occurs on an unoccupied surfacewithincreasing concentrationo fs olute.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the four bi-component systems behaved differently upon thermal annealing treatments. Using Monte Carlo (MC) simulation, [21][22][23][24] we investigated how the dimensionality of the supramolecular structures affects their thermodynamic properties. In particular, the simulations revealed that the structures with different dimensionalities exhibited distinctive specific heat characteristics, [25][26][27] consistent with the experimental observations.…”
Section: Introductionmentioning
confidence: 99%